A welfare analysis of "junk" information and spam filters - Josef Falkinger (University of Zurich, Socioeconomic Institute, 2008)
This paper analyses the equilibrium effects of individual information filters. Information is modelled as advertisements which are distributed across a population of consumers with heterogeneous preferences. An advertisement that provides knowledge about a product with little or no utility for a consumer is considered junk. Filters are characterised by their level of tolerance. The quality of the filter is measured in terms of the share of useful items in the total set of items passing the filter. It is shown that in conditions of decentralised competition, multiple equilibria arise. A social optimum can be achieved by demanding each consumer to reject a certain percentage of advertisements, leaving the choice of what is rejected up to the consumer him/herself.
Keywords: D83; L86; M38; D18; 330; global information society; advertising; junk information; spam filter; internet regulation; Informationsverbreitung; Wissensgesellschaft; Online-Marketing; Internet; Regulierung; Welt